1987
DOI: 10.1104/pp.84.4.1074
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome Oxidase Subunit II Gene from Carrot Contains an Intron

Abstract: Introhs in the cytochrome oxidase subunit II (COXII) gene of plant mitochondrial DNA (mtDNA) have been observed only in monocots. The COXII genes in dicots investigated to date do not contain introns. This is the rirst report of an intron in the COXII gene of a dicot. The presence ofan intron in the carrot COXII intron was verified by restriction mapping and hybridization using specific maize and wheat COXII probes. Regions of the carrot COXII intron are homologous to the maize COXII intron and homologous to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
5
0

Year Published

1989
1989
1993
1993

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…During the analysis of these PCR products using Southern hybridization with synthetic oligonucleotides, the coxII intron was identified and characterized in the following dicot families: Apiaceae, Apocynaceae, Asclepiadaceae, and Solanaceae (Table 2). The present study substantiates the recent reports that the coxII gene from some dicots contains a ricelike intron (Ceci et al, 1987;Turano et al, 1987;Pruitt and Hanson, 1989;Jubier et al, 1990;Senda et al, 1991;Mann et al, 1991;De Bennedeto et al, 1992;Lippok, Brennicke, and Wissinger, 1992) in contrast to the report of Kao, Moon, and Wu (1984) who predicted that dicots lack a coxII intron.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…During the analysis of these PCR products using Southern hybridization with synthetic oligonucleotides, the coxII intron was identified and characterized in the following dicot families: Apiaceae, Apocynaceae, Asclepiadaceae, and Solanaceae (Table 2). The present study substantiates the recent reports that the coxII gene from some dicots contains a ricelike intron (Ceci et al, 1987;Turano et al, 1987;Pruitt and Hanson, 1989;Jubier et al, 1990;Senda et al, 1991;Mann et al, 1991;De Bennedeto et al, 1992;Lippok, Brennicke, and Wissinger, 1992) in contrast to the report of Kao, Moon, and Wu (1984) who predicted that dicots lack a coxII intron.…”
Section: Discussionsupporting
confidence: 87%
“…Pruitt and Hanson (1989) also reported that the petunia intron inserts contain multiple insertions. On the other hand, Turano et al (1987) proposed that deletion of segments of the coxII intron could produce the same result. According to this 'deletion model', the coxII intron-inserts in wheat and rice coxII genes were precursors to the maize coxII intron, and the intron-inserts were lost either by alignment or recombination of the direct repeats.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…A group II intron splits the coxlI gene in several, but not all, plant species that have been examined (Fox and Leaver 1981;Hiesel and Brennicke 1983;Turano et al 1987;Pruitt and Hanson 1989). The…”
mentioning
confidence: 99%